PENYULUHAN DAN PEMBERIAN TABLET ASAM FOLAT BAGI IBU-IBU USIA REPRODUKTIF DI DESA ABIANSEMAL, BADUNG - WIHANDANI, DESAK MADE; BAGIADA, NYOMAN AGUS; SURUDARMA, WAYAN (Buletin Udayana Mengabdi; Vol 5 No 1 (2006): Volume 5 No.1 – April 2006, 2012)
ABSTRACT Folat deficiency that happened during early period of pregnancy, has known as one of the factor that cause fetal abnormalities. That why it is important for pregnant women to get information about the rule of folic acid in preventing fetal abnormalities. From 93 women within reproductive age, 6 of them were pregnant. Pregnant women were given 30 tablets of 0,4 mg folic acid taken once a day, and the less 87 women who were not in pregnant state received 10 tablets of folic acid to be taken once a day. PENYULUHAN DAN PEMBERIAN TABLET ASAM FOLAT BAGI IBU-IBU USIA REPRODUKTIF DI DESA ABIANSEMAL, BADUNG DESAK MADE WIHANDANI, NYOMAN AGUS BAGIADA DAN WAYAN SURUDARMA Bagian Biokimia Fakultas Kedokteran Universitas Udayana ABSTRACT Folat deficiency that happened during early period of pregnancy, has known as one of the factor that cause fetal abnormalities. That why it is important for pregnant women to get information about the rule of folic acid in preventing fetal abnormalities. From 93 women within reproductive age, 6 of them were pregnant. Pregnant women were given 30 tablets of 0,4 mg folic acid taken once a day, and the less 87 women who were not in pregnant state received 10 tablets of folic acid to be taken once a day.